Prediction of the therapeutic response to methotrexate at 24 weeks by methotrexate–polyglutamates concentration in erythrocytes at 8 weeks in patients with rheumatoid arthritis. Issue 3 (4th May 2017) - Murosaki, Takamasa; Nagatani, Katsuya; Sato, Takeo; Akiyama, Yoichiro; Ushijima, Kentaro; Lefor, Alan Kawarai; Fujimura, Akio; Minota, Seiji
Abstract: Objectives : The objective of this study is to evaluate the pharmacokinetics and pharmacodynamics of methotrexate–polyglutamates (MTX-PGs) in erythrocytes in patients with rheumatoid arthritis and correlate them with the efficacy. Methods : MTX-PG concentrations in erythrocytes were measured in 42 MTX-naïve patients repeatedly for 24 weeks by high-performance liquid chromatography. In 56 patients receiving stable MTX doses for at least 12 weeks, the correlation between MTX doses and MTX-PG concentrations was examined. The efficacy was measured by the change of DAS28CRP (ΔDAS28CRP). Results : There were moderate correlations between MTX dose and MTX-PG 3, 4, and 5. At 24 weeks, MTX-PG2, 3, 4, and 1–5 were higher in patients with ΔDAS28CRP >1.2 than in those with ≤1.2. The cutoff value of MTX-PG1-5 to discriminate ΔDAS28CRP >1.2 from ≤1.2 at 24 weeks was 68.7 nM. Among 20 patients with MTX-PG1-5 > 50.6 nM at 8 weeks, seven already improved at 8 weeks and additional 11 improved at 24 weeks ( p  < 0.001). On the contrary, among the nine patients with MTX-PG1-5 ≤ 50.6 nM at 8 weeks, none improved at 8 weeks and only one improved at 24 weeks ( p  = 0.500). Conclusions : Erythrocyte MTX-PGs might be a potential indicator and predictor of MTX efficacy.